ESTRO ACROP guidelines for external beam radiotherapy of patients with complicated bone metastases. (August 2022) - Oldenburger, Eva; Brown, Stephanie; Willmann, Jonas; van der Velden, Joanne M.; Spałek, Mateusz; van der Linden, Yvette M.; Kazmierska, Joanna; Menten, Johan; Andratschke, Nicolaus; Hoskin, Peter
Highlights: Evidence based guidelines on spinal cord compression and neuropathic pain. Evidence based guidelines on pathological fracture prevention and management. Recommendations for technique and dose fractionation. Abstract: This is the second part of the guidelines on the management of bone metastases. In the first part, the diagnosis and management of uncomplicated bone metastases have been addressed. Bone metastases may significantly reduce quality of life due to related symptoms and possible complications. The most common symptoms include pain and neurologic deficits. The most serious complications of bone metastases are skeletal-related events (SRE), defined as pathologic fracture, spinal cord compression, pain, or other symptoms requiring an urgent intervention such as surgery or radiotherapy. Diffuse bone metastases may lead to hypercalcaemia that can be fatal if untreated. The growing access to modern diagnostic tools allows early detection of asymptomatic bone metastases that could be successfully managed with local treatment if oligometastatic or systemic treatment for diffuse bone metastases to try to avoid the development of SRE.